Household size, birth order and child health in Botswana - David Mmopelwa (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2019)
One of the theoretical predictions relating to the family size and birth order effect on child capital is resource dilution hypothesis, according to which large sizes and high child birth order are likely to have negative effects. However, there are arguments that the assumption of a fixed and narrow flow of resources from parents underpinning the theory may not always hold. In Botswana, children aged 6-60 months are eligible for monthly food ration provided through the health care facilities. Notwithstanding this, child health as measured by the three anthropometric indicators: stunting (low height for age), being underweight (low weight for age), and wasting (low weight for height) deteriorated overtime, while on average household size declined. This paper investigates the child birth order and alternative family structure (i.e household) size effect on health. Using the 2009/10 Botswana Core Welfare Indicator Survey (BCWIS) data we estimate the random effects model to explore the within and between household effect. We find that children of high birth order are likely to fare worse than their lower birth order counterparts in nutrition. Household size is negatively associated with child health, and there are higher variances across than within households. Higher variances are unexplained by the observed characteristics. The paper calls for further work on the issue of intrahousehold allocation, to aid evaluation of the program in line with the country's national population policy objective of quality life.
Keywords: I12; J12; J13; 330; Child health; household size; birth order